Assertive Training To Improve Communication And Harmony In Early Marriage: Pelatihan Asertif untuk Meningkatkan Komunikasi dan Keharmonisan pada Penikahan Dini - Velinda, Hilda; Noviekayati, IGAA; Santi, Dyan Evita (Universitas Muhammadiyah Sidoarjo, 2019)
Research on the effectiveness of assertive training to improve communication and early marriage, aims to test the effectiveness of assertive training to improve communication at early marriages and test the effectiveness of assertive training to improve harmony in early marriages, as well as examine differences in improved communication and harmony in early marriages after assertive training . The hypotheses in this study are (1) effective assertive training to improve communication at early marriage (2) assertive training to improve harmony at early marriage. Sampling using purposive sampling, research subjects totaling 10 subjects. The results show that there are significant differences so that it can be concluded that there are (1) effective assertive training to improve communication at early marriage (2) effective assertive training to improve harmony in early marriage.